Estudio, diseño e implementación de un sistema de vigilancia y monitoreo de video en tiempo real, aplicando cámaras análogas y cámaras IP, administradas bajo servidor Linux y Zoneminder, en la unidad educativa particular mixta Bolivariano - Curipoma Quevedo, Henry Mauricio (2013)
This project which is detailed below, was made in the Mixed Individual Educational Unit "Bolivarian" from the city of Machala, educational institution dedicated to high school, but their primary mission is the integral formation of male and female youth Machala canton province and wing with high schools in Technical Sciences.